The sustainability of urban and peri-urban orchards with agroecological base: the case of Quito - Clavijo Palacios, Catalina Elizabeth (2017)
An investigation was carried out on the sustainability of 86 urban and peri-urban orchards in Quito in 2012, framed in three public and private management models. Sustainability was measured through 26 indicators, and 36 economic, environmental, sociocultural and technological sub-indicators, along with qualitative information obtained through semi-structured interviews. Although all the gardens were above the sustainability threshold, there are some aspects that need to be reviewed to improve their performance, related to water, seeds, and technical assistance, among others.